Games and learning (I) (Journal of Parents and Teachers, 2014)
Game is introduced in schools as something beyond fun and enjoyment. Games have a very important educative potential, as with them and thanks to them, everyone can create, invent and experiment. Not only they motivate, but also through games and its different types and versions, people learn and develop skills and abilities.
Keywords: didactics; videogames; learning; game.